VIDEO STEGANOGRAPHY ALGORITHM AND ITS ANALYSIS - Gadgoli Amruta K.; Prof. Wagdarikar A. U. (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Now a day, it’s terribly risky to handle the information in web against intruders. Information is mostly within the type of text, audio, video and image. Steganography is one among the most effective strategies to share the information on the QT and firmly. Steganography algorithmic rule is applied to audio, video and image file. Secret information could also be within the kind of text, image or perhaps within the kind of video and audio. Concealing secret info in video file is understood as video steganography. In this paper varied video steganography techniques and its algorithms has been bestowed.